150k views
1 vote
Simplify to create an equivalent expression2(-2-4p)+2(-2p-1)

User GorillaApe
by
5.4k points

2 Answers

2 votes

Answer:

-12p + −6

Explanation:

Let's simplify step-by-step.

2(−2−4p) + 2(−2p−1)

Distribute:

=(2)(−2) + (2)(−4p) + (2)(−2p) + (2)(−1)

= −4 + −8p + −4p + −2

Combine Like Terms:

= −4 + −8p + −4p + −2

= (−8p + −4p) + (−4 + −2)

= −12p + −6

User Paul McCarthy
by
5.5k points
7 votes

Answer:

Explanation:

Distribute:

=(2)(−2)+(2)(−4p)+(2)(−2p)+(2)(−1)

=−4+−8p+−4p+−2

Combine Like Terms:

=−4+−8p+−4p+−2

=(−8p+−4p)+(−4+−2)

=−12p+−6

User Nif
by
5.3k points